Why Do Payment Card Networks Charge Proportional Fees? - Shy, Oz; Wang, Zhu (American Economic Review, 2011)
This paper explains why payment card networks charge fees that are proportional to the transaction values instead of charging fixed per-transaction fees. We show that, when card networks and merchants both have market power, card networks earn higher profits by charging proportional fees. It is also shown that competition among merchants reduces card networks' gains from using proportional fees relative to fixed per-transaction fees. Merchants are found to earn lower profits under proportional fees, whereas consumer utility and social welfare are higher. Our welfare results are then evaluated with respect to the current regulatory policy debates. (JEL E42, G21, G28)